The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1590/1809-43921981112285
|View full text |Cite
|
Sign up to set email alerts
|

Duas novas espécies de Megacoelium Szidat, 1954 (Trematoda: Heploporidae), parasitas estomacais de peixes da Amazônia Brasileira, com uma redefinição do gênero

Abstract: Duas novas espécies de Megacoelium Szidat, 1954 (T rematada: Heploporidae )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…However, Proteocephalus sp., D. longicauda, G. genarchella and hirudineans only occured in P. braueri, while A. gnerii parasitized only P. pardalis. Pterygoplichthys pardalis from different locations have been parasitized by Unilatus spp., Heteropriapulus spp., Megacoelium spinispecum Thatcher & Varella, 1981, Austrodiplostomum compactum (Lutz, 1928 Dubois, 1970 and Gorytocephalus sp. (Thatcher and Varella 1981;Mendoza-Franco et al 2010;Luque et al 2011;Porto et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Proteocephalus sp., D. longicauda, G. genarchella and hirudineans only occured in P. braueri, while A. gnerii parasitized only P. pardalis. Pterygoplichthys pardalis from different locations have been parasitized by Unilatus spp., Heteropriapulus spp., Megacoelium spinispecum Thatcher & Varella, 1981, Austrodiplostomum compactum (Lutz, 1928 Dubois, 1970 and Gorytocephalus sp. (Thatcher and Varella 1981;Mendoza-Franco et al 2010;Luque et al 2011;Porto et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Pterygoplichthys pardalis from different locations have been parasitized by Unilatus spp., Heteropriapulus spp., Megacoelium spinispecum Thatcher & Varella, 1981, Austrodiplostomum compactum (Lutz, 1928 Dubois, 1970 and Gorytocephalus sp. (Thatcher and Varella 1981;Mendoza-Franco et al 2010;Luque et al 2011;Porto et al 2012). When the same endoparasite is found in more than one host species in the same environment, it indicates the occurrence of new intermediate hosts in the habitat, in addition to the fact that different fish species share one or more food items (Marcogliese 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal organs and the visceral cavity were analyzed under a stereomicroscope. The collected parasites were treated according to Eiras et al (2000) and identified based on Thatcher (1978Thatcher ( , 1979Thatcher ( , 1991Thatcher ( and 1993, Thatcher & Boeger (1984a, b), Thatcher & Varella (1981), Moravec (1998), Takemoto et al (2002) and Lizama et al (2004). The age of each specimen was established according to the growth parameters estimated in Lizama (2000) and applied to obtain the mean length of each age class.…”
mentioning
confidence: 99%
“…Only two parasitological reports have been published in Pterygoplichthys pardalis from its native range (Central Amazonia, Brazil), where a total of 6 helminth species were found: Megacoelium spinicavum (Thatcher & Varella, 1981), Austrodiplostomum compactum, Diplostomum sp., Gorytocephalus sp., Heteropriapulus sp. and Unilatus sp.…”
Section: Discussionmentioning
confidence: 99%